Association between H-type arterial hypertension and vascular stiffness (a pilot study) - Yu. M. Sirenko; O. L. Rekovets; O. O. Torbas; S. M. Kushnir; O. Yu. Sirenko (Zaporožskij Medicinskij Žurnal)
Increased arterial stiffness is an important determinant of cardiovascular risk. Elevated total homocysteine (HC) levels appeared to be an independent risk factor for cardiovascular disease (CVD). To date, clinical studies on the relationship between HC and pulse wave velocity (PWV) assessment have shown conflicting results.